Let's get to learn the particulate structure of matter with augmented reality!: a jigsaw IV technique lesson plan. (3rd April 2022) - Özyalçın, Büşra; Avcı, Filiz
Abstract: The present study aimed to develop, introduce, and conduct an activity for the integration of augmented reality to the jigsaw IV technique in a planned and systematic manner. The activity developed for secondary school students is related to the "Pure Substances" subject which it is included in the "Particulate structure of matter" topic. The activity was arranged as; an attractive introduction, expert group studies, home team studies and assessment stages. Whereas augmented reality was used during the "home team study" stage for the jigsaw IV technique. Students are given the opportunity to examine a lot of resources during the "expert group study" and "home team study" stages to encourage them to be educated as science literate individuals. Whereas the students are subject to individual examinations during the assessment stage. This activity is an example for increasing the usage area of augmented reality in the education environment. Moreover, it is also considered that the activity will provide benefits in ensuring meaningful learning by embodying abstract concepts and helping students in improving 21st-century skills (e.g., cooperative study skills, learning to learn, communication, entrepreneurship, adaptation, leadership, social skills, and responsibility, etc.).